International public administrations in environmental governance - Jörgens, H.; Kolleck, N.; Goritz, A.; Well, M.; Schuster, J.; Saerbeck, B. (Routledge handbook of environmental policy, 2023)
This chapter reviews the most recent advances in the scholarly literature on international environmental bureaucracies and relates it to the long and fruitful research agenda on International Public Administrations (IPAs). We argue that IPAs need to be studied as a distinct class of actors in environmental policy. Section 12.2 defines IPAs as partially autonomous actors and distinguishes them from the wider international organizations or treaty systems that they are an integral part of. Section 12.3 gives examples of IPA influence in environmental governance, while Section 12.4 identifies the underlying causal mechanisms of their influence. Section 12.5 lays out an agenda for the future study of international public administrations in environmental governance.